2014
DOI: 10.3390/nu6020489
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Resveratrol on Biomarkers of Oxidative Stress Induced by Iron/Ascorbate in Mouse Spermatozoa

Abstract: Resveratrol (RVT) is a polyphenolic compound found mainly in the grape and attributed with various pharmacological properties, among them their antioxidant activity. In the present study, we assess the antioxidant activity of resveratrol on oxidative damage induced by ferrous iron/ascorbate (100 µM/150 µM) in sperm of CD1+ mice. We evaluated several parameters in spermatozoa treated with or without resveratrol: (i) sperm quality analysis; (ii) mitochondrial transmembrane potential (Δψm); (iii) ROS generation; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
40
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 50 publications
12
40
1
3
Order By: Relevance
“…Our findings were in line with studies which found resveratrol, as an antioxidant, had good effects on sperm production and motility (Mojica-Villegas et al, 2014). Oxidative stress, lipid peroxidation and changes in membrane properties induced by morphine resulted in the death of germ cells and reduced the sperm morphology and motility (Venkatesh et al, 2009), while antioxidants like resveratrol protected sperms from damage induced by free radicals through scavenging them (Ourique et al).…”
Section: Discussionsupporting
confidence: 80%
“…Our findings were in line with studies which found resveratrol, as an antioxidant, had good effects on sperm production and motility (Mojica-Villegas et al, 2014). Oxidative stress, lipid peroxidation and changes in membrane properties induced by morphine resulted in the death of germ cells and reduced the sperm morphology and motility (Venkatesh et al, 2009), while antioxidants like resveratrol protected sperms from damage induced by free radicals through scavenging them (Ourique et al).…”
Section: Discussionsupporting
confidence: 80%
“…One of the most widely used techniques to assess semen oxidative status is the measurement of lipid peroxidation by-products after incubation with an OS promoter system, thus evaluating sperm susceptibility to an oxidative environment (Aitken et al 1993, Bansal & Bilaspuri 2008, Simõ es et al 2013, Mojica-Villegas et al 2014. In rams, there is little data about the OS effect on sperm DNA packaging and fragmentation, especially under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, resveratrol may decrease germ cell apoptosis [174,175]. At the same time, Mojica-Villegas et al [138] and Shin et al [173] showed that resveratrol has the capacity to inhibit mitochondrial ROS production, disruption of membrane potential and permeability transition, thereby protecting the key intracellular organelle against the oxidative stress promoted by FeAA. Moreover, resveratrol has a cytoprotective effect against iron-related oxidative burst, as illustrated by the inhibition of apoptosis and alterations in apoptotic markers [173].…”
Section: Antioxidantsmentioning
confidence: 99%
“…Finally, lipid peroxidation as a consequence of the Fecatalyzed Fenton reaction was previously observed in human [137], mouse [138], goat [139], bovine [140] and equine spermatozoa [141].…”
Section: Coppermentioning
confidence: 99%